Nanotherapy silencing the interleukin‐8 gene produces regression of prostate cancer by inhibition of angiogenesis. Issue 4 (18th July 2016) - Aalinkeel, Ravikumar; Nair, Bindukumar; Chen, Chih‐Kuang; Mahajan, Supriya D.; Reynolds, Jessica L.; Zhang, Hanguang; Sun, Haotian; Sykes, Donald E.; Chadha, Kailash C.; Turowski, Steven G.; Bothwell, Katelyn D.; Seshadri, Mukund; et al.
Summary: Interleukin‐8 (IL‐8) is a pro‐angiogenic cytokine associated with aggressive prostate cancer (CaP). We detected high levels of IL‐8 in sera from patients with CaP compared with healthy controls and patients with benign prostatic hypertrophy. This study examines the role of IL‐8 in the pathogenesis of metastatic prostate cancer. We developed a biocompatible, cationic polylactide (CPLA) nanocarrier to complex with and efficiently deliver IL‐8 small interfering RNA (siRNA) to CaP cells in vitro and in vivo . CPLA IL‐8 siRNA nanocomplexes (nanoplexes) protect siRNA from rapid degradation, are non‐toxic, have a prolonged lifetime in circulation, and their net positive charge facilitates penetration of cell membranes and subsequent intracellular trafficking. Administration of CPLA IL‐8 siRNA nanoplexes to immunodeficient mice bearing human CaP tumours produced significant antitumour activities with no adverse effects. Systemic (intravenous) or local intra‐tumour administration of IL‐8 siRNA nanoplexes resulted in significant inhibition of CaP growth. Magnetic resonance imaging and ultrasonography of experimental animals demonstrated reduction of tumour perfusion in vivo following nanoplex treatment. Staining of tumour sections for CD31 confirmed significant damage to tumour neovasculature after nanoplex therapy. These studies demonstrate the efficacy of IL‐8 siRNA nanotherapy for advanced, treatment‐resistant human CaP. Abstract : Our study demonstrates the translational potential of a nanoparticle based drug delivery as a promising new tool for the safe and effective delivery of IL‐8 siRNA to CaP tumors to inhibit angiogenesis and concomitant tumor growth. Cationic polylactide (CPLA) based interleukin ‐8 (IL‐8) siRNA nanoplexes administered to mice showed no evidence of toxicity or induction of inflammation. They also exhibited strong antitumor activity in a mouse model of human prostate cancer (CaP) after local or systemic administration.